FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS HIDUP (QUALITY OF LIFE) PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA - apriliana; Hendra Kusumajaya; Rima Berti Anggraini (Journal Of Nursing Science Research, 2024)
Patients suffering from chronic kidney failure and undergoing hemodialysis will experience disturbances in various aspects of their lives, including physical, psychological, social, and environmental which will ultimately affect their quality of life. This study aims to determine the factors associated with the quality of life of patients with chronic kidney failure undergoing hemodialysis. The research method is quantitative research with a cross-sectional approach. The sample in this study was 90 respondents. The sampling technique used in this study was non-probability sampling using a purposive sampling technique. Data analysis used the Spearman rho test. The results of this study found that the factors related to the quality of life in chronic kidney failure patients undergoing hemodialysis with a ? ? value of 0.00 (<0.005) and r value = 0.866, anxiety with a ? ? value of 0.00 (<0.005 and r value ? 0.655, and depression with a ? ? value of 0.00 (<0.005) and r value = 0.644. The suggestion from this study is that the results of this study are expected to be used as literature and references to improve the quality of life in chronic kidney failure patients, especially in the psychological aspect.